Harvesting Lithium: water, brine and the industrial dynamics of production in the Salar de Atacama. Issue 119 (February 2021) - Bustos-Gallardo, Beatriz; Bridge, Gavin; Prieto, Manuel
Abstract: Geographical research on lithium and other renewable energy materials explores the geopolitical dimensions of resource supply and the 'new geographies' associated with an expanding resource frontier. The material characteristics and environmental conditions of lithium production, however, are largely overlooked in this perspective. In the context of a global speculative boom for lithium linked to its growing role in energy storage, this paper adopts a grounded, exploratory approach to investigate the dynamics of production and resource management at one of the world's most significant sources of lithium: the brine deposits of the Atacama Salt Flat/Salar de Atacama in northern Chile. We show how lithium production from brine has a distinctive 'eco-regulatory' character as it involves managing a series of hydrogeological conditions and physical processes that are largely external to capital. The paper highlights the infrastructures (pumps, pipes, ponds) associated with the harvesting of lithium from brine and examines how production on the salar generates a series of ecological contradictions (notably around water depletion) with potential to disrupt accumulation. We also examine the multiple flexibilities afforded by the eco- regulatory character of production, and show how these enable lithium producers to adapt fixed infrastructures to dynamic political economic conditions. By focusing on both contradictions and flexibilities of lithium production, the paper draws attention to trajectories of capitalisation in the lithium value chain and their environmental consequences; and considers the political-economic incentives shaping further capitalisation. The paper concludes by considering the implications of this exploratory case study for critical resource geography.